A review of association and linkage studies for genetical analyses of learning disorders - Caylak, Emrah (Wiley, 2007)
Learning disorders (LD) commonly comprise of a heterogeneous group of disorders manifested by unexpected problems in some children's experiences in the academic performance arena. These problems especially comprise of a variety of disorders which may be subclassified to attention-deficit hyperactivity disorder (ADHD), reading disability (RD), specific language impairment (SLI), speech-sound disorder (SSD), and dyspraxia. The aim of this review is to summarize the current molecular studies and some of the most exciting recent developments in molecular genetic research on LD. The findings for the association and linkage of LD with candidate genes will help to set the research agendas for future studies to follow. (c) 2007 Wiley-Liss, Inc.
Keywords: attention-deficit hyperactivity disorder (ADHD); reading disability (RD); specific language impairment (SLI); speech-sound disorder (SSD); dyspraxia